( a 8 + b 8 + c 8 + d 8 + e 8 ) ( a 1 1 + b 1 1 + c 1 1 + d 1 1 + e 1 1 )
If a , b , c , d , e are the roots of x 5 + 7 x − 1 = 0 , then find the value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Exactly the same way, Dev Sharma , here is the link add it as inspiration https://brilliant.org/problems/can-this-be-really-solved/?group=hg2ab1j7ZuLk&ref_id=985738
Log in to reply
Log in to reply
while edit use \ [\ #Inspiration#\ ]\ \ (\ #https://brilliant.org/problems/can-this-be-really-solved/?group=hg2ab1j7ZuLk&ref_id=985738# \ )\, remove blackslashes and hashes, you should also refer to formatting guide
Log in to reply
@Department 8 – Hey, Lakshya, you posted a inequality question. Then please mention in the question about what decimal place we have to provide answer?
Log in to reply
@Dev Sharma – what was the question name
Log in to reply
@Department 8 – cool inequality. Making it really tough
Nice observation!!
Can we directly rise it to x^12 say coefficient of x^11 is absent so sum would be zero.......... Is it correct
Here,
e 1 = ∑ a = 0
e 2 = ∑ a b = 0
e 3 = ∑ a b c = 0
e 4 = ∑ a b c d = 0
e 5 = ∑ a b c d e = a b c d e = 1
Let's calculate P 8 first.
P 8 = e 1 P 7 − e 2 P 6 + e 3 P 5 − e 4 P 4 + e 5 P 3
Since, e 1 , e 2 , e 3 , e 4 are all 0 and e 5 being 1 , we get P 8 = P 3
P 3 = e 1 P 2 − e 2 P 1 + e 3 P 0
Since, e 1 , e 2 , e 3 are all 0 , P 3 = 0
⟹ P 8 = 0
Notice, P 8 is in multiplication with P 1 1 .
Hence our answer is 0 .
e 4 is not 0
e4 is 7 while p11 is 0
anata wa baku desu
How p4 became zero is not clear at all also e4 is not zero
Log in to reply
It most definitely is, p4 is zero using vieta's formulae.
Problem Loading...
Note Loading...
Set Loading...
first lets compute p 1 1 . note that s 1 = s 2 = s 3 = 0 , hence giving us p 1 = p 2 = p 3 = 0 where s n is the nth symmetric sum and p n the nth power sum. we get that . x 5 = − 7 x + 1 x 1 0 = 4 9 x 2 − 1 4 x + 1 x 1 1 = 4 9 x 3 − 1 4 x 2 + x ∑ ( x 1 1 ) = 4 9 ∑ ( x 3 ) − 1 4 ∑ ( x 2 ) + ∑ ( x ) = 4 9 p 3 − 1 4 p 2 + p 1 = 0 since one part of the product is 0, the whole thing becomes 0